THE EFFECT OF OPERATING CASH FLOW, ACCOUNTING PROFIT, AND COMPANY SIZE ON STOCK RETURNS IN MANUFACTURING COMPANIES IN THE BASIC MATERIAL SECTOR LISTED ON THE IDX IN 2020-2021 - Waysul Kuroni; Sri Zulaihati; Ati Sumiati (Transpublika Publisher, 2023)
This study aims to investigate the influence of Operating Cash Flow, Accounting Profit, and Company Size on Stock Returns. The data collection method employed in this research is the documentation study method. The population in this study comprises basic material companies listed on the Indonesia Stock Exchange (IDX) in 2020-2021, totaling 88 companies. Data were obtained by collecting annual financial report data from company websites on the Indonesia Stock Exchange (IDX). This research utilizes purposive sampling techniques, resulting in a sample of 52 companies that meet the specified criteria. Data analysis techniques employed include multiple linear regression analysis, descriptive statistical analysis, prerequisite analysis tests, classic assumption tests, and hypothesis testing. Multiple linear regression analysis reveals relationships among the variables. Descriptive statistical analysis provides an overview of each variable. Prerequisite analysis tests confirm the normal distribution of data. Classic assumption tests confirm that the data are acceptable. The research findings indicate that company size has a positive influence on stock returns, while operating cash flow and accounting profit do not significantly affect the company's value. Furthermore, the coefficient of determination in this study is 1.5%, indicating the ability of operating cash flow, accounting profit, and company size to influence stock returns, while the remainder is influenced by other unexamined factors. This research aims to enhance future company value and suggests that future researchers explore different indicators or company size factors that affect stock returns.